Physico-Chemical Properties of LiM0.10Mn1.90O4 (M: Co, Ni, Cr) for Potential Cathode Materials - Purwaningsih, Dyah; Roto, Roto; Sutrisno, Hari; Purwanto, Agus (Asian Journal of Chemistry, 2017)
Transition metal-doped spinel cathode materials of LiM0.1Mn1.9O4 (M: Co, Ni, Cr) were prepared by solid-state reaction. The structure and morphology of the products were investigated by X-ray photoelectron spectroscopy, X-ray diffraction, Rietveld refinement and SEM-EDX. The oxidation states of Mn, Co, Ni and Cr were found to be 3+/4+, 2+, 2+ and 3+, respectively as revealed by X-ray photoelectron spectroscopy. SEM-EDX shows uniform particles and the particle size was about 200-700 nm ranges. The diffraction peaks of the prepared solids corresponded to a single phase of cubic spinel structure with a space group Fd3m. Doping of Co, Ni and Cr causes lattice parameters to decrease. The prepared materials have ionic conductivity where LiCo0.10Mn1.90O4 has the highest capacitance.